Transforming health and well‐being through publishing computable biomedical knowledge (CBK) - Güneş Koru (Wiley, 2023)
Abstract Computable biomedical knowledge artifacts (CBKs) are software programs that transform input data into practical output. CBKs are expected to play a critical role in the future of learning health systems. While there has been rapid growth in the development of CBKs, broad adoption is hampered by limited verification, documentation, and dissemination channels. To address these issues, the Learning Health Systems journal created a track dedicated to publishing CBKs through a peer‐review process. Peer review of CBKs should improve reproducibility, reuse, trust, and recognition in biomedical fields, contributing to learning health systems. This special issue introduces the CBK track with four manuscripts reporting a functioning CBK, and another four manuscripts tackling methodological, policy, deployment, and platform issues related to fostering a healthy ecosystem for CBKs. It is our hope that the potential of CBKs exemplified and highlighted by these quality publications will encourage scientists within learning health systems and related biomedical fields to engage with this new form of scientific discourse.